Circulating isoflavone and lignan concentrations and prostate cancer risk: a meta‐analysis of individual participant data from seven prospective studies including 2, 828 cases and 5, 593 controls. Issue 11 (29th September 2018) - Perez‐Cornago, Aurora; Appleby, Paul N.; Boeing, Heiner; Gil, Leire; Kyrø, Cecilie; Ricceri, Fulvio; Murphy, Neil; Trichopoulou, Antonia; Tsilidis, Konstantinos K.; Khaw, Kay‐Tee; Luben, Robert N.; Gislefoss, Randi E; et al.
Abstract : Phytoestrogens may influence prostate cancer development. This study aimed to examine the association between prediagnostic circulating concentrations of isoflavones (genistein, daidzein, equol) and lignans (enterolactone and enterodiol) and the risk of prostate cancer. Individual participant data were available from seven prospective studies (two studies from Japan with 241 cases and 503 controls and five studies from Europe with 2, 828 cases and 5, 593 controls). Because of the large difference in circulating isoflavone concentrations between Japan and Europe, analyses of the associations of isoflavone concentrations and prostate cancer risk were evaluated separately. Prostate cancer risk by study‐specific fourths of circulating concentrations of each phytoestrogen was estimated using multivariable‐adjusted conditional logistic regression. In men from Japan, those with high compared to low circulating equol concentrations had a lower risk of prostate cancer (multivariable‐adjusted OR for upper quartile [Q4] vs . Q1 = 0.61, 95% confidence interval [CI] = 0.39–0.97), although there was no significant trend (OR per 75 percentile increase = 0.69, 95 CI = 0.46–1.05, p trend = 0.085); Genistein and daidzein concentrations were not significantly associated with risk (ORs for Q4 vs . Q1 = 0.70, 0.45–1.10 and 0.71, 0.45–1.12, respectively). In men from Europe, circulating concentrations of genistein, daidzein and equol were not associated with risk. Circulating lignan concentrations were not associated with the risk of prostate cancer, overall or by disease aggressiveness or time to diagnosis. There was no strong evidence that prediagnostic circulating concentrations of isoflavones or lignans are associated with prostate cancer risk, although further research is warranted in populations where isoflavone intakes are high. Abstract : What's new? The role of phytoestrogens in prostate cancer development is uncertain. Here, the authors analysed participant data from seven prospective studies on the association between pre‐diagnostic circulating concentrations of isoflavones (mainly found in soybeans) and lignans (mainly found in cereal, nuts, and vegetables) and prostate cancer risk. They found no strong associations but point to the fact that further data are needed to examine associations based on disease aggressiveness, especially in populations with high isoflavone intakes.